The Increasing of N, P, and K Nutrient in Palm Oil Under Prenursery Seedling By Application of Palm Oil Waste Compost and Endofitic Microbes - Hamidah Hanum; Lisnawati Lisnawati; Ahmad Rafiqi Tantawi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Improvement of palm oil   nutrient  status  since at the nursery is one of the efforts to improve plant resistance to Ganoderma attacks. Compost from palm oil waste and potentially endophytic microbes could  potentially  increase  plant  nutrients,  especially  N,  P  and  K.  This  study  aims  to  determine  the potential of oil palm waste compost and endophytic microbes in increasing N, P and K in the plant oil palm under  prenursery seedling. The study was conducted in a factorial experiment with the factors tested  were  types  of  compost,  type  and  time  of  endophytic  microbial  inoculation.  Research  results indicating  that  the  levels  of  N,  P  and  K  plants  are  not  affected  by  the  main  factors  and  factor interactions of three factors. The concentration of of N, P, K soil is influenced by the interaction effect of two factors. The empty fruit bunch compost enriched every type endophyte showed better effects than  compost  midrib  in  increasing  levels  of  P  and  K  nutrient  in    plants  and  plant  growth  The application  endofitic  microbe    after  and  before  Ganoderma  application      inreased    phosphor  and potassium in plant and growth plant.